Characterization of voluntary termination of pregnancy in adolescents at the "Fe del Valle Ramos" Hospital - Yunior Meriño Pompa; Sulanys Yainet Naranjo Vázquez; Olegario Leyva Escalona; Mirtha Johnson Quiñones; Giselle Lucila Vázquez Gutiérrez (Universidad Médica Pinareña, 2022)
Introduction: voluntary termination of pregnancy in adolescents is a problem that affects reproductive health in different sectors of society.